Kedudukan Hukum Pembagian Harta Warisan pada Perempuan di Minangkabau dengan Sistem Matrilineal Ditinjau dari Hukum Islam - Salsabilla Putri Ananda; Husni Syawali (Bandung Conference Series: Law Studies, 2024)
ABSTRACT The Minangkabau kinship system, which adheres to a matrilineal descent, especially in the context of inheritance division, presents a unique situation due to the differences between Minangkabau customary law, which values female heirs, and the Islamic inheritance law, which is bilateral. Despite the philosophy of "Adat Basandi Syarak, Syarak Basandi Kitabullah" emphasizing adherence to Islamic Sharia in customs, distinctions arise, particularly concerning the role of women in the ownership and management of inheritance. This research aims to identify the factors that lead to women in Minangkabau receiving more inheritance than men, and to examine the impact from an Islamic legal perspective. The research methodology employed is qualitative normative, utilizing primary, secondary, and tertiary literature data. The research findings indicate that the main factor for women in Minangkabau receiving more inheritance is their elevated status as holders of "amban puruak" and their right to use the inherited property. The distribution of inheritance to women is considered a form of family endowment (wakaf) that holds significant benefits in supporting the economic livelihood of Minangkabau women